Histologic effects of mandibular protrusion splints in antigen-induced TMJ arthritis in rabbits - Julia von Bremen; Kernt Köhler; Krystyna Siudak; Daniel Zahner; Sabine Ruf (BMC, 2017)
Abstract Background Although it is common clinical practice to treat children with Juvenile Idiopathic Arthritis (JIA) with functional appliances, the scientific evidence for this is limited. The aim of this study was to study the histologic effects of mandibular protrusion splints in temporomandibular joint (TMJ) arthritis in rabbits. Methods Twenty-eight ten-week old New Zealand white rabbits were randomly divided into four groups: AO (TMJ arthritis, no splint), AS (TMJ arthritis, mandibular splint advancement), OS (no arthritis, mandibular splint advancement) and OO (no arthritis, no splint). TMJ arthritis was induced in the groups AO and AS; 1 week later mandibular protrusion splints were placed on the upper incisors of the AS and OS animals. After 60 days the animals were sacrificed and a semiquantitative histologic evaluation of each TMJ was carried out to analyze the amount of inflammation and bone modeling. Results AO and AS animals had a higher inflammation score (AO = 1.3; AS = 1.8) than the non-arthritis groups (OO = 0.6; OS = 0.4). Whereas in the untreated control (OO) the amount of apposition and resorption was almost in balance (+1), OS animals displayed significantly more apposition (+9) and AO animals significantly more resorption (−3) than the untreated control. Arthritis animals with protrusion appliances (AS), however, had remarkably more bone apposition (+3) than resorption, indicating a similar bony reaction as in healthy animals, although reduced in extent. Conclusions Mandibular advancement in rabbits with TMJ arthritis is possible without detrimental histologic reactions and appears to partially compensate for the bone loss seen in rabbits with TMJ arthritis but without protrusion splints.